Study on ductile-brittle transition of single crystal silicon by a scratching test using a single diamond tool - Mukaiyama, Koki; Ozaki, Mitsunori; Wada, Tadahiro (2017 8th International Conference on Mechanical and Aerospace Engineering (ICMAE), 2017)
Single crystal silicon is a popular material used for semiconductor circuits and solar batteries. In the cutting process from a silicon ingot to a silicon wafer used as semiconductor materials, a multi-wire saw with fixed diamond abrasive grains is widely used due to recent increases in wafer size and reductions in wafer thickness. Also, single crystal silicon can achieve ductile mode cutting when the cutting depth is less than the critical cutting depth for the ductile-brittle transition point (dc). Thus, a silicon wafer with a good surface condition can be obtained by ductile mode cutting. In this study, we conducted scratch tests of single crystal silicon using a single crystal diamond tool. The purpose of this study is to conduct basic studies for improvement of a multi-wire saw. Also, dc was measured while scratch speeds (Vc) were changed. Moreover, we examined the relationship between Vc and cutting resistances (thrust force) at that time. The following results were obtained: 1) dc is not dependent on scratch speeds. 2) In plastic flow in ductile mode cutting, scratch marks were observed. 3) dc is about 0.5 μm at room temperature. 4) Thrust force at the ductile-brittle transition decreases by increasing the scratch speeds.